Analisis Risiko Kebakaran Di Bandar Udara RR Menggunakan Metode FMEA - Mardhiah Gani; Aprisa Rian Histiarini; Asih Ahistasari; raymans Wariori (Metode : Jurnal Teknik Industri, 2023)
Risk is "the possibility of an event occurring that can affect the achievement of organizational goals", this shows that the need for awareness and prevention of fires needs to be increased. Risk control is an action taken to save the company from losses, by determining the best way to deal with risk. Failure Mode and Effect Analysis (FMEA) is a method of evaluating the possibility of a failure of a system, design, process or service to make steps for handling it. The main objective of FMEA is to identify and prevent disturbances by knowing the risks that may occur and developing strategies to reduce these risks. There are three components that will assist in determining the priority of disturbances, namely: a. Frequency (occurrence) b. Level of Damage (severity) c. Detection level (detection). Based on the results of data processing, there are 8 highest risk levels from the RPN, the largest is 213.33 and the RPN with a moderate risk level is 76. Meanwhile, the highest fire risk level from the largest RPN is 193.33 and the RPN with a medium risk level is 110.